Organic carbon contents and stocks in particle size fractions of a typic hapludox fertilized with pig slurry and soluble fertilizer Teores e estoques de carbono orgânico em frações granulométricas de latossolo fertilizado com dejeto suíno e adubo solúvel - Mafra M.S.H. (2015)
© 2015, Revista Brasileira de Ciencia do Solo. All rights reserved.The use of pig slurry (PS) as fertilizer can affect the soil quality and increase total stocks of soil organic carbon (TOC). However, the effects of PS on TOC amount and forms in the soil are not fully understood, particularly in areas under no-tillage (NT). The purpose of this study was to determine TOC contents and stocks in the particulate (POC) and mineral-associated C fractions (MAC) of an Oxisol after nine years of maize-oat rotation under NT, with annual applications of PS, soluble fertilizer and combined fertilization (pig slurry + soluble fertilizer). The experiment was initiated in 2001 in Campos Novos, Santa Catarina, with the following treatments: PS at rates of 0 (without fertilization - PS0); 25 (PS25); 50 (PS50); 100 (PS100); and 200 m3 ha−1 yr−1 (PS200); fertilization with soluble fertilizer (SF); and mixed fertilization (PS + SF). The TOC content was determined in samples of six soil layers to a depth of 40 cm, and the POC and MAC contents in four layers to a depth of 20 cm. From the rate of 50 m3 ha−1 yr−1 and upwards, the soil TOC content and stock increased according to the PS rates in the layers to a depth of 10 cm. The POC and MAC contents and stocks were higher in the surface layers, with a clear predominance of the second fraction, but a greater relative amplitude in the contents of the first fraction.